THE RADIATION DOSE PROFILE IN PEDIATRIC INTERVENTIONAL CARDIOLOGY TO ESTIMATE THE STOCHASTIC EFFECT RISK: PRELIMINARY STUDY - Muqmiroh, Lailatul; Praptono, Soegardo Indra; Rusmanto, Rusmanto; Latifah, Risalatul; Sensusiati, Anggraini Dwi (Journal of Vocational Health Studies, 2018)
Background: The specific characteristic of anatomy and physiology of children cause the risk of radiation effects received when they underwent the interventional cardiology procedures higher than an adult. Purpose: to estimate the stochastic effect risk in a pediatric patient during interventional cardiology procedures. Method: Data collection was performed by placing thermoluminescence dosimeter (TLD) on thyroid, gonad, left and right thoracic areas, and the 5th thoracic vertebrae during interventional cardiology. Result: The results showed that the greatest exposure was received around vertebrae (bone marrow) because of the superimpose X-ray on the vertebrae during the procedures. Conclusion: The greatest probability of stochastic effect that happened was leukemia. Estimation risk ratio of leukemia was 0, 9 % and thyroid cancer was 0,037%.